Community participation in community share ownership trusts in Bikita rural district of Zimbabwe - Nechena, Herbert; Kurebwa, Jeffrey (Sryahwa Publications, 2018)
This study focused on the participation of communities in Community Share Ownership Trusts (CSOTs) with specific reference to Bikita rural district in Zimbabwe. Qualitative methodology was used for the study. Key informant interviews and semi-structured interviews were used to gather data with various respondents from Bikita rural district.Community participation in CSOTs has far-reaching effects on development in Zimbabwe. It stimulates broad-based participation at community level and catalyses development through CSOTs.Conditions such as clarification of the roles of communities in the CSOTs, an effective legal framework which empower communities and making communities active participants in decision-making especially on development projects should be met in order for community participation to be effective. These conditions do not only promote effective participation but facilitate economic empowerment of local communities in rural areas.
Keywords: Community share ownership trusts; Empowerment; Development; Community participation